Geopolitical Risk and Macroeconomic Spillovers in a Frontier Market: The Sectoral Transmission of the US–Iran–Israel Conflict to Ethiopia - Belay Sitotaw Goshu (Rowter Journal, 2026)
The escalating geopolitical tensions between the United States, Iran, and Israel in 2025–2026 have generated significant global economic disruptions through oil price volatility, maritime chokepoint closures, and trade route diversions. Frontier markets, particularly landlocked, net oil-importing economies, face asymmetric vulnerability to such distant geopolitical shocks. This study examines the transmission channels and sectoral impacts of the US–Iran–Israel geopolitical conflict on Ethiopia's economy, providing a disaggregated analysis of how the shock propagates across productive sectors. Drawing on projections from the International Monetary Fund, the World Bank, national authorities, and sectoral reports, the analysis employs a qualitative and analytical approach, synthesizing available data to construct a comprehensive sectoral impact assessment across energy, maritime trade, agriculture, industry, transport, construction, and household welfare. Findings: The conflict transmits through four primary channels; energy prices, maritime logistics, agricultural inputs, and remittances. While Ethiopia's GDP growth remains robust at 9.2 percent, inflation has accelerated to 13.9 percent, reversing prior moderation. The fiscal position faces strain from increased subsidy outlays, and the birr faces persistent depreciation pressure. Agriculture confronts acute vulnerability through fertilizer shortages (a 68%channels: urea price surge) and elevated shipping costs; the industry faces rising energy costs and supply chain bottlenecks; transport experiences soaring operational costs; and urban households bear the regressive burden of rising food prices, with 15–15. 9 million people are facing a crisis or emergency food insecurity. Ethiopia's experience exposes profound structural vulnerabilities characteristic of frontier markets. The crisis offers a strategic opportunity to accelerate the renewable energy transition, diversify supply chains, and strengthen macroeconomic buffers. Recommendations: Policymakers should establish strategic fuel reserves, diversify port access and fertilizer sources, maintain fiscal consolidation while protecting pro-poor expenditures, and adequately fund social safety nets. Channels: